Recovering adsorptive properties of schungite after processing red beet juice - Melnyk, Lyudmila; Melnyk, Zinoviy (My University, 2013)
When producing food dye from red beet juice part of impurities, especially pectin substances, is adsorbed by the carbon adsorbent - shungite, containing fullerenes and fullerene nanotubes. During adsorption of red beet juice, surface and pores of shungite are filled with impurities, resulting in decrease of its adsorptive properties.The purpose of the present studies was to select an effective method for regeneration of adsorbent and to establish rational technological parameters of this process.When choosing a method of regeneration, the authors of this paper were motivated by economic feasibility and took into account the availability of necessary equipment at canning factories.
Keywords: beet juice; adsorption; regeneration; shungite; сік столового буряка; адсорбція; регенерація; шунгіт; сок столовой свеклы; адсорбция; регенерация; шунгит; кафедра процесів і апаратів харчових виробництв; кафедра теплоенергетики та холодильної техніки